Lumped parameter method of permanent magnet synchronous generator for wind energy - Oner, Yasemin; Senol, Ibrahim (SPRINGER, 2016)
The breakthroughs in permanent magnet synchronous machines through the latest technologies, especially about machine design, raise the importance of those machines. Moreover, developments in materials technology implement the development of cost effective and profitable products on electric machines. Permanent magnet synchronous machines are divided into two parts according to the situation of slot/pole combination, which is integer or fractional. Permanent magnet synchronous machines are subject of interest due to low torque ripple and low cogging torque. In this paper, the 2D lumped parameter method (LPM) of permanent magnet synchronous machine was composed and stated, and lumped parameter was verified by finite element method. When SMC materials are used in electric machines, flux flows in 3D. Because of this and according to literatures, 3D method is used to analyze the SMC-used machines. 3D finite element method takes a quite long time. Thanks to 2D LPM analysis, which was used in our work; the analysis period become remarkably shorter. In addition, torque and back EMF of permanent magnet synchronous machine were calculated through the developed LPM method. Prototype is tested. It is seen by the results that the produced prototype and the developed algorithm are matching properly.
Keywords: Lumped parameter method; Permanent magnet machine; Wind energy; Soft magnetic composite; EQUIVALENT-CIRCUIT; AUTOMATIC-GENERATION; MACHINES; OPTIMIZATION; MODELS; Engineering